Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1177/107769908105800418
|View full text |Cite
|
Sign up to set email alerts
|

Factor Study of Dimensions of Advertiser Credibility

Abstract: 4 Bcrlo. Lcmcrt and Mcrtz, op. dr.; Markham. op. cir.; McCroskey. op. cir.; McCroskey and Jenson op. cil.; Singlctary. op. cir.; Whitehead. op. cir. ' Jerry R. Lynn, "Perception of Public Service Advertising: Source. Message and Receiver Effects." JOUKNALISM QUAK-TEKLY. 50:673-679 (Winter 1973); Jerry R. Lynn. Robert 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Communication researchers have been especially interested in the characteristics of message sources that inspire perceptions of credibility (Johnson and Kaye 2002; Meyer 1988; West 1994) and the effects of these perceptions (Kiousis 2001). Researchers have examined source credibility issues in the domains of advertising (Becker, Martino, and Towers 1976; Goldsmith, Lafferty, and Newell 2000; Gotlieb and Sarel 1991; Kamins et al 1989; Kertz and Ohanian 1992; VandenBergh, Soley, and Reid 1981), political persuasion (Chebat, Filiatrault, and Perrien 1990), news reporting (Slater and Rouner 1996), and food labels (Mazis and Raymond 1997). Communication researchers have also examined the influence on perceptions of credibility of the medium through which a source's messages are delivered, including the Internet (Abel and Wirth 1977; Durand, Teel, and Bearden 1979; Flanagin and Metzger 2000; Gantz 1981; Johnson and Kaye 2002; Slater and Rouner 1996).…”
Section: Web Site Credibility and Trustworthinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication researchers have been especially interested in the characteristics of message sources that inspire perceptions of credibility (Johnson and Kaye 2002; Meyer 1988; West 1994) and the effects of these perceptions (Kiousis 2001). Researchers have examined source credibility issues in the domains of advertising (Becker, Martino, and Towers 1976; Goldsmith, Lafferty, and Newell 2000; Gotlieb and Sarel 1991; Kamins et al 1989; Kertz and Ohanian 1992; VandenBergh, Soley, and Reid 1981), political persuasion (Chebat, Filiatrault, and Perrien 1990), news reporting (Slater and Rouner 1996), and food labels (Mazis and Raymond 1997). Communication researchers have also examined the influence on perceptions of credibility of the medium through which a source's messages are delivered, including the Internet (Abel and Wirth 1977; Durand, Teel, and Bearden 1979; Flanagin and Metzger 2000; Gantz 1981; Johnson and Kaye 2002; Slater and Rouner 1996).…”
Section: Web Site Credibility and Trustworthinessmentioning
confidence: 99%
“…Buying via the Internet entails several consumer risks and vulnerabilities (e.g., not being able to examine a product before buying it, not knowing where a retailer is located, having to submit credit card and other sensitive personal information to a faceless entity). Given these vulnerabilities, sellers must inspire consumer trust before an Internet transaction is likely to occur (see, for example, Bryant and Colledge 2002; Castelfranchi and Tan 2002; Head and Hassanein 2002; Jarvenpaa and Tractinsky 1999; Lee and Turban 2001; Urban, Sultan, and Qualls 2000; Wang 2001; Warrington, Abgrab, and Caldwell 2000).…”
Section: Web Site Credibility and Trustworthinessmentioning
confidence: 99%
“…They found that highly experienced users may be overly skeptical and that inexperienced users tend to over-rely on suggestions from computers, as compared to a control condition with mimeographed lists of the same suggestions. This finding fits with an early belief among researchers that users are likely to be "in awe" of computers, viewing them as credible in a wide range of domains (Pancer, 1992), but later experiments show little evidence for this belief (Andrews and Gutkin, 1991;Waern and Ramberg, 1996 (Singletary, 1976) and (Vandenbergh, Soley, and Reid, 1981) asked participants in their studies to imagine a specific high-credibility source (in Singletary's case, a news person; in VandenBergh et al's, an advertiser) and to list as many terms as possible that, in the participant's view, gave credibility to that source. Other researchers either sampled the existing literature to create a list of candidate terms based upon their review or relied upon intuition.…”
Section: Contexts Affect Credibility Constructssupporting
confidence: 76%
“…Although originally developed to assess psychological adjustment and complexes (Jung, 1910(Jung, , 1918, word association tests have been used to study meanings, world views, stereotypes, and brand images (Szalay and Kelly, 1982;Moodie et al, 1995;Gordon, 1962;McDowell, 2004). Vicary (1948) and Vandenbergh et al (1981) used word association to understand the meanings of "advertising" and "advertisers." McDowell (2004) used word association to assess brand images of cable news programs.…”
Section: Epistemological Issuesmentioning
confidence: 99%